Respuesta :
1. Domain.
We have [tex]x^2-2x-3 [/tex] in the denominator, so:
[tex]x^2-2x-3\neq0\\\\(x^2-2x+1)-4\neq0\\\\(x-1)^2-4\neq0\\\\(x-1)^2-2^2\neq0\qquad\qquad[\text{use }a^2-b^2=(a-b)(a+b)]\\\\(x-1-2)(x-1+2)\neq0\\\\ (x-3)(x+1)\neq0\\\\\boxed{x\neq3\qquad\wedge\qquad x\neq-1}[/tex]
So there is a hole or an asymptote at x = 3 and x = -1 and we know, that answer B) is wrong.
2. Asymptotes:
[tex]f(x)=\dfrac{x-3}{x^2-2x-3}=\dfrac{x-3}{(x-3)(x+1)}=\boxed{\dfrac{1}{x+1}}[/tex]
We have only one asymptote at x = -1 (and hole at x = 3), thus the correct answer is A)
We have [tex]x^2-2x-3 [/tex] in the denominator, so:
[tex]x^2-2x-3\neq0\\\\(x^2-2x+1)-4\neq0\\\\(x-1)^2-4\neq0\\\\(x-1)^2-2^2\neq0\qquad\qquad[\text{use }a^2-b^2=(a-b)(a+b)]\\\\(x-1-2)(x-1+2)\neq0\\\\ (x-3)(x+1)\neq0\\\\\boxed{x\neq3\qquad\wedge\qquad x\neq-1}[/tex]
So there is a hole or an asymptote at x = 3 and x = -1 and we know, that answer B) is wrong.
2. Asymptotes:
[tex]f(x)=\dfrac{x-3}{x^2-2x-3}=\dfrac{x-3}{(x-3)(x+1)}=\boxed{\dfrac{1}{x+1}}[/tex]
We have only one asymptote at x = -1 (and hole at x = 3), thus the correct answer is A)
The given function has a hole at (x = 3) and an asymptote at (x = -1) and this can be determined by using the given data.
Given :
[tex]\rm f(x) = \dfrac{x-3}{x^2-2x-3}[/tex]
The following steps can be used in order to determine the true statement about the given function:
Step 1 - Write the given function.
[tex]\rm f(x) = \dfrac{x-3}{x^2-2x-3}[/tex]
Step 2 - The denominator of the following function never be zero.
[tex]x^2-2x-3\neq 0[/tex]
[tex]x^2-3x+x-3\neq 0[/tex]
[tex]x(x-3)+1(x-3)\neq 0[/tex]
[tex](x-3)(x+1)\neq 0[/tex]
Step 3 - Now, simplify the given function.
[tex]\rm f(x) = \dfrac{x-3}{(x-3)(x+1)}[/tex]
[tex]\rm f(x) = \dfrac{1}{x+1}[/tex]
Step 4 - So, the asymptote is given below:
x + 1 = 0
x = -1
Therefore, the correct option is A).
For more information, refer to the link given below:
https://brainly.com/question/15324782